The classical Doppler effect revisited by the mathematical description of the phase function - Alejos, Óscar; Muñoz, José María (2023)
This paper aims to shed some more light on one of the best known phenomena in the field of physics, the Doppler effect, in particular, on its classical version. Although, as mentioned, it is a phenomenon already described more than 150 years ago, the general case, even considering constant velocities, continues to be the subject of very recent bibliographical works which either show it incompletely or start from a not entirely accurate description of it. Here, general expressions of both frequency shift and aberration are obtained by geometrical description and, more interestingly, by describing the phase of the wave in the reference frame in which the propagating medium is at rest. The coherence between the two points of view permits to contrast the validity of the proposed results, and allows for a generalization of the resulting expressions for any reference frame, even those where the propagating medium is not still.